2020
DOI: 10.1007/s12571-020-01121-z
|View full text |Cite
|
Sign up to set email alerts
|

Food waste in Italian households during the Covid-19 pandemic: a self-reporting approach

Abstract: Food waste prevention and reduction are an economic, social and environmental concern included among the 17 Sustainable Development Goals (SDGs) within Agenda 2030 for Sustainable Development. The third target under SDG 12 (Target 12.3) on Responsible Production and Consumption aims to halve food waste by 2030 at retail and consumer levels, considering that more than half of its quantity is generated by final consumers, both indoor and outdoor. However, the Covid-19 pandemic outbreak at the beginning of 2020 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 51 publications
6
96
1
Order By: Relevance
“…Another longitudinal research carried out by the International Food Information Council (IFIC) ( 47 ) on American consumers has shown that, although the perception of importance of achieving an environmental sustainability was stable compared to past years, the COVID-19 pandemic has led American consumers to becoming better aware about the impact of individuals' decisions in achieving the sustainable goals. Furthermore, an Italian study ( 48 ) has analyzed how the fear of reduced food availability during the COVID-19 pandemic has led consumers to better preserve and manage purchased food products, by reducing the extent of food waste. Very similar results were achieved in Qatar where the COVID-19 pandemic has not only greatly reduced food waste but has also drastically changed the consumption behavior of people who have purchased more healthier and sustainable products ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another longitudinal research carried out by the International Food Information Council (IFIC) ( 47 ) on American consumers has shown that, although the perception of importance of achieving an environmental sustainability was stable compared to past years, the COVID-19 pandemic has led American consumers to becoming better aware about the impact of individuals' decisions in achieving the sustainable goals. Furthermore, an Italian study ( 48 ) has analyzed how the fear of reduced food availability during the COVID-19 pandemic has led consumers to better preserve and manage purchased food products, by reducing the extent of food waste. Very similar results were achieved in Qatar where the COVID-19 pandemic has not only greatly reduced food waste but has also drastically changed the consumption behavior of people who have purchased more healthier and sustainable products ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Planning food purchases contributes to the purchase of better ingredients and menu organization, with the addition of avoiding overselling, cooking in large quantities and generating leftovers [26,41]. Likewise, the behavior in the store influences the amount of waste [14,28,50,51] and people who buy impulsively waste more [50].…”
Section: Routines Of Food Purchase On Salementioning
confidence: 99%
“…Understanding these factors benefits society in general in the sense of identifying the economic value of waste, emissions generated in production, and management of waste and its final destination, which is considered a main aspect to improve food security and environmental sustainability [11,16,18,24,25]. Apart from this, the prevention and reduction in food wastage is a Sustainable Development Target [26]. However, the studies are dissimilar, with different methodologies and a variety of approaches, which makes it a challenge to compare their results [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to fill the lack in the literature, the authors investigate the active role of smart working, the change in food purchase habits, the improvement in food delivery and the opportunities offered by improved time management. Since entire countries remained under lockdown, millions of people had enough time to learn and/or improve food planning and storage operations, adopted a possible food program (diet), increased time allotted for eating and improved cooking skills, familiarizing themselves at the same time with domestic appliances never used due to exaggerated dynamic lifestyles [37]. Thus, the COVID-19 pandemic has brought new challenges, and opened new paths and opportunities for food waste reduction.…”
Section: Food Waste Behavior At Households: Literature Backgroundmentioning
confidence: 99%
“…The present paper, on the basis of a previous study on food waste among Italian households, which highlighted novel work-life balances, adequate time management and smart food delivery as good answers toward food waste reduction at households [37], explores the issue further at local scale. Through an online questionnaire and a k-means cluster analysis at the regional level, the authors investigate four constructs: a) consumer environmental concern (i.e., knowledge on food waste-related losses in terms of energy, natural resources and financial opportunities, as well as perception of climate change); (b) time management, distinguishing between shopping planning, diet planning, culinary activities management and time allotted for eating; (c) price/quantity consciousness; and (d) influence of the COVID-19 pandemic on food consumption and food waste behavior.…”
Section: Introductionmentioning
confidence: 99%